Global Competition and Ways to Ensure Business Competitiveness - Run Zhang; Natalia Karmina (Communications of International Proceedings, 2021)
In the era of globalization and the domination of world monopolies, competition in international relations is growing and its forms are becoming tougher. Global competition becomes a form of international competition in which the position of an enterprise in one country affects its competitive position in other countries. As a result, companies are competing among themselves for international leadership. As a result of such a struggle, the economy is globalizing. The preservation and strengthening of the positions of the business is realized through increasing their competitiveness. In the context of global uncertainty, the level of economic security of a company should ensure the preservation and strengthening of its positions both in the domestic and international markets. All this makes it possible to defend against emerging threats, respond to new challenges and develop sustainably. The higher the level of development of the factors that determine the competitiveness of a company, the more stable and viable it is in the face of constantly emerging external and internal threats. At the same time, one should not forget about competitors, who represent the most important component of the external microenvironment of any company. Therefore, in market conditions, the success of any company significantly depends on how competitive its products, goods or services are and what actions the company takes to maintain it in the changing conditions of the modern market. Thus, ensuring the required level of competitiveness is the main strategic task of any company, especially in a rapidly changing market in the context of the global crisis caused by the pandemic. In order to successfully operate in a highly competitive market and maintain the required level of competitiveness, companies are mastering new types of services, introducing new forms of doing business, stimulating their employees and fighting to attract each client. When planning its activities, the company takes into account not only the needs of customers, but also the strategies of competitors. Based on the information received in the course of studying the conditions of competition, the strategy of the enterprise for the development of the market is largely formed, as well as the general strategy of the enterprise. The article deals with the issues of global competition and ways to ensure the competitiveness of business. The following tasks were solved in the article: study the theoretical aspects of competitiveness; analyze the Chinese company Lenovo in the international market explore Lenovo's competitive strategy in the global international market. In this article, the authors attempt to analyze the basic principles of company competition in the international market of international companies. The article examines various sources of information, analysis of the information received, methods of analysis and synthesis, study and generalization, classification.
Keywords: Competition; international market; business; competitiveness; strategies.